Authentic Materials in Reading Comprehension Classroom: Its Effectiveness to Indonesian EFL Students Achievement - Assiddiq, Muhammad Azwar (Universitas Malikussaleh, 2019)
The study was aimed to finding out (1) Whether or not the use of authentic materials is effective to develop the reading comprehension achievement of Indonesian EFL Students, (2) Whether or not the use of authentic materials is effective to develop reading motivation of Indonesian EFL Students. The study was carried out under the quantitative paradigm with quasi experimental design. The participants were selected by using cluster sampling technique and divided into two groups, namely authentic group and pedagogic group. Each of groups consisted of 39 participants. All participants were first grade students of high school in Bone, Indonesia. The data of the students reading comprehension achievement were collected by using reading comprehension test, while the data about the students reading motivation were taken from Motivation for Reading Questionnaire (MRQ) containing 32 items on seven domains of motivation. The data collected were then analyzed through descriptive and inferential statistics through SPSS 20 program. The result showed that (1) the use of authentic materials was effective than pedagogic materials to develop reading comprehension achievement of the first year students. It was seen from the significance t-test result that reveals the significance value was lower than the significance level; (0.00 < 0.05). Furthermore, in relation to the reading motivation of students, (2) it was found that authentic materials was effective to develop students reading motivation. The result showed that the p-value of students reading motivation before and after treatments was greater than the level of significance (0.00 < 0.05).